The RTS,S malaria vaccine: Journey from conception to recommendation - Oluwaseyi Muyiwa Egbewande (Elsevier, 2022)
The RTS,S malaria vaccine was recently recommended for use among children at risk in malaria endemic regions. Although significant efforts have been made to minimise malaria cases, the results of these innovations have not been totally satisfactory due to specific limitations. However, this revolutionary vaccine has a great tendency to put an end to malaria. Being the first vaccine against malaria, this commentary examines its journey from the idealisation and conception to the recommendation by the World Health Organization. The commentary also examines some of the challenges that might affect the execution of the vaccination programme in sub-Saharan Africa and other malaria endemic regions and suggest recommendations to overcome the possible them.